PENGENALAN KECERDASAN MAJEMUK UNTUK EFEKTIVITAS PENDAMPINGAN BELAJAR ANAK DI DESA DURUNG BEDUG - Achmad Dhany Fachrudin (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2018)
This Program aims is to overcome the problems of most parents, who have difficulty in assisting children when learning. One of it is they do not understand the type of their children’s intelligence. Forcing children to learn something that is not their interests indirectly will make they more difficult to understand what he learned. From the results of activities undertaken, it is known the average Durung Bedug residents do not know what is a multiple intelligence. They just assume that a smart child is a child who gets academic achievement in school. Therefore, many children are considered stupid by his parents just because they lack in math in his school. They do not realize that it could be that their children have other potential intelligences that are very likely to be developed. And through this activity has been obtained the commitment of citizens to pay more attention to the potential intelligence of their children and help develop it.